Redução do torque concêntrico e isométrico de joelho e tornozelo em indivíduos diabéticos não é dependente da presença de polineuropatia - Ferreira, Jean de Paula (2016)
Contextualization: The Diabetes Mellitus (DM) is an epidemic disease in the world and stay associated with right index of morbidity and mortality and about 90% of cases of DM are type 2 (DM2). DM2 develop by inflammatory mechanisms carrying the insulin resistance and consecutively blond hyperglycemia. Believes that in chronic stages the diabetes causes musculoskeletal dysfunctions can be related to inflammatory and metabolic alterations of the DM2 or with diabetic polyneuropathy. Some studies identified the musculoskeletal alteration in diabetic subjects. However not is clearly if the polyneuropathy cause muscle alteration proportionality sensitive alterations. Also weren’t observed studies that analyzed the torque in subjects with DM2, considering others factors that could influence the muscle torque production and also not were observed studies analyzing the torque in diabetic subjects during different types of contractions (concentric, eccentric and isometric). Objectives: The aim of the present study were analyze the torque at concentric eccentric and isometric muscle contractions in diabetic subject with and without polyneuropathy comparing with a control groups. Methods: The peak torques of flexion and extension were acquired using an isokinetic dynamometer, in sitting position. During concentric and eccentric contractions, the joint speed was set at 60°/s. Five maximal voluntary contractions were acquired for concentric and eccentric and 2 for isometric, with a rest interval of 1.5 minutes. The sequence of the tests was randomized and verbal and visual feedback were standardized and delivered to all subjects by the same person. Three groups of adult males were selected for this study (1) Control group (healthy non-diabetic patients, n=33), (2) Diabetic group (patients with diabetes mellitus without polyneuropathy, n=31), (3) Neuropathic group (patients with diabetic polyneuropathy, n=28). The Neuropathic group was defined according to a fuzzy model of signs and symptoms. Differences between groups were calculated with one way ANOVA for parametric knee variables (α of 5%) and Mann Whitney and Willcoxon for non-parametric ankle variables (adjusted α of 1.6%). To describe effect sizes, Hedges’ g was calculated. Results: Irrespective of polyneuropathy, both diabetic groups presented lower peak torques of knee and ankle, both for isometric contraction and for concentric flexion and extension. Other factors beside the polyneuropathy and early in the diabetes onset, may be influencing in the muscle strength production. The eccentric contraction was not different between any groups.